Microbe‐mediated control of Aspergillus flavus in stored rice grains with a focus on aflatoxin inhibition and biodegradation. (14th August 2017) - Mannaa, M.; Oh, J.Y.; Kim, K.D.
Abstract: Biological control of mycotoxigenic fungi using antagonistic microbes is a promising alternative to agricultural chemicals for postharvest storage. In this study, we evaluated rice‐derived bacterial strains to identify biocontrol agents to inhibit Aspergillus flavus in stored rice grains. Consequently, we obtained three potential biocontrol strains ( Microbacterium testaceum KU313, Bacillus megaterium KU143 and Pseudomonas protegens AS15) from 26 tested strains that were prescreened from the 460 strains isolated from rice grains. The three selected strains proved to be effective biocontrol agents showing antifungal activity against A. flavus and good colonisation ability on rice grains, along with inhibition of the fungal growth and aflatoxin production. In particular, P. protegens AS15 greatly inhibited the aflatoxins produced by A. flavus on rice grains to 8.68 (percent aflatoxin reduction relative to control = 82.9%) and 18.05 (68.3 %) ng g −1 dry weight of rice grains, compared with the 50.89 and 56.97 ng g −1 dry weight of rice grains of the MgSO4 control at 1 and 2 weeks after inoculation, respectively. In addition, strain AS15 had a significant ability to not only degrade aflatoxin B1 (the most harmful aflatoxin), but also utilise the toxin for bacterial growth in a nutrient‐deficient medium. Therefore, the selected bacterial strains could be environmentally sound alternatives for the management of A. flavus and aflatoxin production by reducing the fungal damage to stored rice grains. This would also reduce the human and animal health hazards associated with the consumption of fungus‐contaminated rice grains. To our knowledge, this is the first report of the potential of the bacterial species M. testaceum and P. protegens as biocontrol agents for controlling aflatoxigenic A. flavus on stored rice grains. Abstract : (A) Aflatoxin degradation by bacterial strain AS15, strain KU408 (negative control), and MgSO4 (untreated control) in various diluted nutrient broth supplemented with aflatoxin B1 at 3 days after inoculation; (B) bacterial populations of the treatments in the diluted medium with or without aflatoxin B1 .